Analisis Kemampuan Berpikir Tingkat Tinggi dan Literasi Biologi Siswa pada Materi Virus di Kelas X SMA Negeri 1 Labuhan Deli - Ryandi Ihsan; Hasruddin (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to investigate the high-order thinking skills (HOTS), biological literacy, and the relationship between HOTS and biological literacy of Grade X students at SMA Negeri 1 Labuhan Deli regarding virus material. A sample of 36 students was randomly selected for this quantitative research, employing a descriptive quantitative method. Data collection techniques included interviews, documentation, and tests. Data analysis was conducted using statistical methods, particularly descriptive statistics. The findings revealed that students’ HOTS fell into the “good” category with scores ranging from 61 to 80, with the highest percentage of indicator occurrence (76.9%) for evaluating problems. Regarding biological literacy, students demonstrated a “very good” level of understanding in evaluating explanations (83.9%). In the aspect of conducting procedures, students achieved a “good” level (63.7%), while in explaining phenomena, they reached a “fairly good” level (46.4%). A positive correlation was found between HOTS and biological literacy in Grade X students’ understanding of viruses.